Organization of independent educational and cognitive activities of students of art faculties of higher education institutions in the process of studying conducting and choral disciplines : Technological aspect - Kostenko, Lyudmila (Professional Art Education, 2023)
The purpose of the article is  theoretical justification and clarification and experience of using technological aspects of the organization of independent educational and cognitive activities of students in the process of studying conducting and choral disciplinesMethods and methodology . The research is based on the leading positions of scientists regarding the organization of independent educational and cognitive activities students of art faculties of ZVO, taking into account the technological aspect.The scientific novelty of the article lies in the generalization and experience of organizing independent educational and cognitive activities of students of art faculties . Offered implement systems of innovative learning technologies in order to ensure a high professional qualification level of graduates, in accordance with the requirements of modern standards of higher education.Results. The stages of studying conducting and choral disciplines in the conditions of the implementation of KMS are considered: diagnostic (determining the level of musical-theoretical and practical training of a beginner student); organizational (development of forms and methods of independent conducting and choral training); management (creation of external and internal conditions that regulate the process of individualization of students' independent work). The proposed approach to the organization of educational and cognitive activities of students is considered in the context of the development of creative independence of choirmaster teachers.
Keywords: independent work; learning strategy; content of conducting and choral training; structuring the content of educational material; innovative teaching methods